2022
DOI: 10.1017/neu.2022.12
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social isolation due to the COVID-19 pandemic on patients with dementia and caregivers

Abstract: Objective: Social distancing to limit COVID-19 transmission has led to extensive lifestyle changes, including for people with dementia (PWD). The aim of this study, therefore, was to assess the impact of lockdown on the mental health of PWD and their carers. Methods: Forty-five carers of PWD completed a telephone interview during the baseline assessment of the SOLITUDE study to gather information on life conditions and changes in symptoms of PWD during lockdown. Associations between chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…This interview included questions on patients, living conditions and socialisation before lockdown, carers’ personal mental health problems experienced and help received during lockdown, as well as carer-reported changes in PWD’s symptoms during lockdown (up to T0). Findings from the carer semi-structured interview have already been reported in Manca et al ( 26 ). For the purpose of this study, only carer-reported changes in existing neuropsychiatric and cognitive symptoms, the emergence of new neuropsychiatric symptoms and carers’ concerns about progression of dementia were considered, among the variables collected as part of this customised interview, as predictors of all of the outcome measures.…”
Section: Methodssupporting
confidence: 53%
See 3 more Smart Citations
“…This interview included questions on patients, living conditions and socialisation before lockdown, carers’ personal mental health problems experienced and help received during lockdown, as well as carer-reported changes in PWD’s symptoms during lockdown (up to T0). Findings from the carer semi-structured interview have already been reported in Manca et al ( 26 ). For the purpose of this study, only carer-reported changes in existing neuropsychiatric and cognitive symptoms, the emergence of new neuropsychiatric symptoms and carers’ concerns about progression of dementia were considered, among the variables collected as part of this customised interview, as predictors of all of the outcome measures.…”
Section: Methodssupporting
confidence: 53%
“…Demographic and clinical characteristics of all PWD and carers are reported in Table 1 . The majority of patients received a clinical diagnosis of Alzheimer’s disease and the carer was their spouse/partner in most cases [for more details on our sample see ( 26 )].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean age of the care recipients ranged from 70.0 to 81.4 years. 29,35 Five studies reported on informal carers of individuals with mild, moderate, or severe dementia (see Table 1). 8,17,18,32,41…”
Section: Caregiver's and Care Recipient's Characteristicsmentioning
confidence: 99%